Effect of level of competition and drill typology on internal and external load in male volleyball players during the preseason period - Kerpe, G.; Zuoza, A. K.; Conte, D. (International Journal of Sports Physiology and Performance, 2024)
Purpose This study aimed at evaluating the effect of level of competition and drill typology on loads during the preseason period in male volleyball players.